P205 The impact of the severity of microscopic inflammation at the time of diagnosis on UC-related outcomes during follow-up. (25th January 2019) - Frias Gomes, C; Ellul, P; Almeida, A; Morão, B; Gouveia, C; Callé, C; Buhagiar, T; Attard, A; Branco, J; Rodrigues, J; Teixeira, C; Castro, F; et al.
Abstract: Background: Several studies have reported that the presence of histological inflammation in patients with ulcerative colitis affects prognosis and important UC-related outcomes. However, the prognostic value of histological inflammation at the time of diagnosis is not well characterised, and histology is not currently used to assess prognosis in UC patients. Our aim was to review the microscopic features at the time of UC diagnosis, and to assess its prognostic value during follow-up. Methods: Multi-centre restrospective study. Biopsies obtained from the rectum in newly-diagnosed, treatment-naïve patients with proctitis (E1) and left-sided colitis (E2) were obtained. Pathology slides were reviewed by two independent pathologists and classified according to the Nancy score, grading from 0 (mild chronic inflammation) to 4 (ulcers). The impact of the severity of inflammation at diagnosis on a composite outcome (need for hospitalisation, steroids, and therapy escalation, acute severe UC or proximal disease extension) was evaluated using chi-square analysis. Wilcoxon test was performed to evaluate the performance of Nancy score in time to an adverse outcome. Results: Forty patients were included (56.3% men, median age at diagnosis 47 years [17–66], median follow-up 1389 days [67–9836]). 64.6% were classified as proctitis (E1) and 35.4% as left-sided colitis (E2). Histological features found in inflamed rectal mucosa were marked chronic inflammation in 75%, moderate-to-severe basal plasmocytosis in 70.9%, moderate to severe neutrophils invasion in lamina propria in 60.5%, moderate-to-severe mucin depletion in 79.2% and ulcers in 27.1%. During the follow-up, 13/48 cases had an adverse outcome: 7/48 needed steroids, 2/48 were hospitalised, 1/48 had an acute episode of severe UC, 4/48 had proximal endoscopic extension and 9/48 escalated therapy. Moderate to severe histological features were more frequent in patients who were hospitalised (2/2), had disease extension (4/4) and needed steroids (basal plasmocytosis (6/7), neutrophils in lamina propria (5/7) and mucin depletion (6/7). In a composite endpoint no significant association was found with basal plasmocytosis ( p = 0.18), mucin depletion ( p = 0.17) and neutrophils invasion in lamina propria ( p = 0.60). In the subgroup of patient developing an adverse outcome during follow-up, the median time to an adverse event was lower in Nancy scores ≥3 (781 vs. 1567 days, p < 0.001). Conclusions: In our cohort of newly diagnosed patients severe histological inflammation at the time of diagnosis, as assessed by the Nancy score, was associated with a lower median time to an adverse outcome, suggesting that histological information should also be incorporated to guide prognosis assessment and therapeutic choices.